The Analysis Effect of Traffic Acces at AH. Nasution and STM Street - Lubis, Marwan; Tanjung, Darlina; Batu Bara, Hamidun; Husni Malik Hasibuan, M; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
The impact of the construction of an activity center will create awakening and attraction traffic and also increase negative impact to the flow of traffic access, safety, comfortable to pedestrian, the surrounding will be influenced by building development or building activities. The analysis result has been done is know the V/R ratio of street especially at segment 4 in 2019. The  ratio of the service indicators is at level E. Instability condition of the traffic access that often stop with the average speed of the vehicle about 28.5 km/h, while the volume road performence in 2024 or after the student’s building has operated about 5 years was predicted  the service indicators is at level F, its mean forced flows or jammed, low speed capacity and long vehicle and became a big obstacle, while another access is at e level especially at segment 2 for A H Nasution access and segment 3 at STM street access.